Density Dependence Drives Habitat Production and Survivorship of Acropora cervicornis Used for Restoration on a Caribbean Coral Reef - Ladd, Mark C.; Shantz, Andrew A.; Nedimyer, Ken; Burkepile, Deron E. (Frontiers in Marine Science, 2016)
Coral restoration is gaining traction as a viable strategy to help restore degraded reefs. While the nascent field of coral restoration has rapidly progressed in the past decade, significant knowledge gaps remain regarding the drivers of restoration success that may impede our ability to effectively restore coral reef communities. Here, we conducted a field experiment to investigate the influence of coral density on the growth, habitat production, and survival of corals outplanted for restoration. We used nursery-raised colonies of Acropora cervicornis to experimentally establish populations of corals with either 3, 6, 12, or 24 corals within 4m2 plots, generating a gradient of coral densities ranging from 0.75 corals m−2 to 12 corals m−2. After 13 months we found that density had a significant effect on the growth, habitat production, and survivorship of restored corals. We found that coral survivorship increased as colony density decreased. Importantly, the signal of density dependent effects was context dependent. Our data suggest that positive density dependent effects influenced habitat production at densities of 3 corals m−2, but further increases in density resulted in negative density dependent effects with decreasing growth and survivorship of corals. These findings highlight the importance of density dependence for coral restoration planning and demonstrate the need to evaluate the influence of density for other coral species used for restoration. Further work focused on the mechanisms causing density dependence such as increased herbivory, rapid disease transmission, or altered predation rates are important next steps to advance our ability to effectively restore coral reefs.